Effects of glucose rinsing on mood after helping - Law, Xin Ning (2014)
The present study explored whether glucose rinsing has any effect on mood changes, particularly in positive affect (PA) and negative affect (NA) after engaging in prosocial behavior. The study used a 2 (Glucose Rinse vs. Non-Glucose Rinse) x 2 (Autonomous Helping vs. Controlled Helping) between-subjects design. Participants’ mood and wellbeing changes were measured before and after the experiment. In the study, participants are given a 5-minute perceptual vigilance task, which they had to cancel out all the e’s in the passage to deplete self control. After which, the participant was asked to rinse with a glucose or non-glucose solution depending on which condition they were assigned to prior to the study. After that, they were given 7-8 minutes of rest time in which, coincidentally, a confederate enters the experimenter room to ask the participant to engage in a spontaneous helping task. Results showed that participants in the Non-Glucose condition had greater post NA regardless of whether they had an autonomous or controlled motive to help. Moreover, there is also a significant interaction between glucose rinsing and helping motive such that in autonomous helping situations, a non-glucose rinse will be more effective than a glucose rinse in enhancing PA after helping. Whereas, in controlled helping situations, a glucose rinse will be more effective than a non-glucose rinse in enhancing PA after helping. These findings suggest that the type of rinse (glucose vs. non-glucose) work differently with regards to affect changes in different helping motives. Limitations and future research implications are also discussed.